1995
DOI: 10.1074/jbc.270.13.7717
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Naturally Occurring Vascular Endothelial Growth Factor · Placenta Growth Factor Heterodimer

Abstract: Vascular endothelial growth factor (VEGF) is a potent and selective mitogen for endothelial cells that is angiogenic in vivo and induced by hypoxia. A homologous protein, placenta growth factor (PlGF), is also reported to be mitogenic for endothelial cells in culture. The rat GS-9L glioma cell line produces not only VEGF homodimers but also PlGF homodimers and a novel heterodimer composed of VEGF and PlGF subunits. All three dimeric forms were purified to apparent homogeneity, and their structures and mitogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
142
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(151 citation statements)
references
References 37 publications
6
142
0
2
Order By: Relevance
“…Furthermore, a PlGF variant, unable to bind FLT1 but still capable of heterodimerizing with VEGF, also inhibited VEGF-and PlGF-dependent angiogenesis in cancer (Tarallo et al 2010). It should be noted, however, that the precise role of the VEGF:PlGF heterodimers remains a matter of debate, as several other studies reported proangiogenic-not antiangiogenic-effects of these heterodimers in vitro and in vivo (DiSalvo et al 1995;Cao et al 1996a,b;Autiero et al 2003). So far, little/nearly nothing is known about the proangiogenic or antiangiogenic activity of naturally occurring VEGF:PlGF heterodimers in physiological settings in vivo.…”
Section: Molecular Mechanismsmentioning
confidence: 83%
“…Furthermore, a PlGF variant, unable to bind FLT1 but still capable of heterodimerizing with VEGF, also inhibited VEGF-and PlGF-dependent angiogenesis in cancer (Tarallo et al 2010). It should be noted, however, that the precise role of the VEGF:PlGF heterodimers remains a matter of debate, as several other studies reported proangiogenic-not antiangiogenic-effects of these heterodimers in vitro and in vivo (DiSalvo et al 1995;Cao et al 1996a,b;Autiero et al 2003). So far, little/nearly nothing is known about the proangiogenic or antiangiogenic activity of naturally occurring VEGF:PlGF heterodimers in physiological settings in vivo.…”
Section: Molecular Mechanismsmentioning
confidence: 83%
“…Interestingly, recent studies describing the existence of VEGF⅐PlGF heterodimers further extend the concept that structural heter- ogeneity may be responsible for a graded biological response. While the PlGF homodimer had minimal endothelial cell mitogenic activity compared to that of the VEGF homodimer, the heterodimer displayed intermediate activity (34). With respect to proteolytic digestion resulting in the generation of VEGF 110 from VEGF 165 or VEGF 189 , little is known at this time about the prevalence of this process in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of purified protein was determined using the Bio-Rad protein assay reagent (Bio-Rad, Hercules, CA, USA) with serially diluted BSA as standard (Conn et al 1990, Houck et al 1992, Disalvo et al 1995. Biological activity of this VEGF protein was demonstrated by competition with binding of recombinant 125 I-VEGF 165 to HUVECs and by its ability to stimulate proliferation of these cells (Nagy et al 1995).…”
Section: Measurement Of Local Edema Formation In Rabbit Skinmentioning
confidence: 99%